What is Semagystia clathrata (Christoph, 1884) (Lepidoptera, Cossidae: Cossinae)? - Yakovlev, Roman V. (Acta Biologica Sibirica, 2022)
The article gives a redescription of the little studied species, Semagystia clathrata (Christoph, 1884) (Lepidoptera, Cossidae: Cossinae). For the first time, we provide the images of the male and female adults from various portions of the distribution range, and describe the male genitalia. The species is reported for the first time for the fauna of Kazakhstan (Mangystau Region). The species distribution map is presented, the article is illustrated with nine figures.